Social Stratification Reflected At Jane Austen's Pride And Prejudice Novel (1813): A Sociological Approach - Hariyanti, Mei, Dr. M. Thoyibi, M.S (2014)
The study is about social stratification in English society in early nineteenth century reflected at Jane Austen's Pride and Prejudice novel. The objectives of the study are to analyze novel based on its structural elements and to analyze the novel based on the sociological approach, by identifying the relation between the novel and the social background of the early nineteenth century in English society based on sociological approach. This research paper belongs to qualitative research. The sources of the data are both primary data source, which is Pride and Prejudice novel. Secondary data sources, are other sources related to the analysis such as books of literary theory of sociological approach and virtual references. The method of data collection is documentation research. The technique of data analysis is descriptive analysis. Based on the analysis, the researcher draws some conclusions. Firstly, based on the structural analysis of the novel it can be concluded that in Pride and Prejudice, Jane Austen conveys a moral message that some people use marriage to lift up their social economic status. Secondly, based on the sociological analysis, it can be concluded that in Pride and Prejudice Jane Austen reflects the social realities of the English society including social, economic, political, science and technology, cultural and religious aspect at late eighteenth century and early nineteenth century.